Adaptive Shapers of Orthogonal Signal Components for Microprocessor Protections - F.` A. Romanjuk; A. V. Rozhdestvensky (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers adaptive shapers of orthogonal components of microprocessor protections of electrical installations. An algorithm for calculation of shapers of orthogonal signal components has been developed. In order to obtain frequency and dynamic characteristics of the shapers calculation experiments have been carried out. The obtained results of calculations demonstrate improvement quality of shaper characteristics.